Alterações de padrão de sono, bruxismo e disfunção temporomandibular em usuários de êxtase: um estudo controlado - Simi, Roberta [UNIFESP] (2010)
Users of MDMA (methylenedioxymethamphetamine), a drug popularly known as ecstasy, report feeling tension in the muscles of the face and bruxism in effect of the drug. We compared a group of users of ecstasy (57 people) to a group of non-users (57 persons) in relation to the presence of changes in architecture or sleep disturbances (by polysomnography), signs and symptoms of temporomandibular disorders (TMD evaluated by the RDC - Research Diagnostic Criteria), bite force, pattern and context of use of ecstasy and other psychoactive substances and associate problems (measured by DUSI-R - Drug Use Screening Inventory Revised). Volunteers were people aged 18 to 40 years, of both sexes, with natural dentition and no history of trauma (cervical or facial), hormonal or neurological disorders, or psychoactive substances dependence (except ecstasy in the experimental group) and not were using drugs acting on the central nervous system. The group of ecstasy users had a higher percentage of stage 3 sleep, less time awake, high number of oxygen desaturations, increased number of episodes of periodic legs moviments, the greater presence of snoring and bruxism phasic. No were found clinically significant differences between groups in symptoms of TMD. The ecstasy users also had higher rates of problems with the use of other psychoactive substances, a higher proportion of relationship problems and adjustment to work. Among users of ecstasy users who were also at risk of alcohol, the presence of bruxism was more pronounced. This confirms in part the association between use of ecstasy and bruxism, which is more evident under the influence of drugs and more rare in the period after cessation of use.